Endobronchial nocardial infection. Issue 12 (December 1993) - McNeil, K D; Johnson, D W; Oliver, W A
Abstract : The rare presentation of nocardial infection as an endobronchial "tumour" is reported. Haematogenous dissemination occurred after fibreoptic bronchoscopy and biopsy, a phenomenon not previously described in nocardial infections. This case highlights the difficulties in diagnosing pulmonary nocardial infection and the potential for invasive procedures to disseminate the disease.